Protecting future rights for future citizens: children's property rights in fragile environments. (2nd October 2018) - Joireman, Sandra F.
Abstract: The property rights of children is an understudied area that straddles the development/humanitarian divide. Access to assets is important to the livelihood choices and economic well-being of adults. Yet, adults' ability to claim property can be significantly impaired by humanitarian emergencies that occurred in their youth. We typically do not think of children as economic actors because of their age; their property rights are future rights not yet realized. This paper addresses the future rights to property held by children and examines how fragile environments, characterized by conflict, displacement and disease, can undermine their ability to claim those rights when they become adults, thus depriving them of assets. We identify two types of responses that can begin to address this problem: (1) legal changes to protect children's assets when guardianship is lost; and (2) actions that can be taken by humanitarian organizations to identify children's assets and protect them through conflict and displacement. This is a particularly salient topic at the current time when the numbers of displaced people are higher than any time previously recorded, and half of the displaced are children.